Environmental and economic assessment of rural domestic waste gasification models in China. (December 2022) - Liu, Hanqiao; Liu, Tong; Wei, Guoxia; Zhao, Hailong; Li, Tong; Weng, Fangkai; Guo, Xin; Wang, Yanzhang; Lin, Yanfei
Graphical abstract: Highlights: Village, town and county models with three gasification scales were compared. The environmental impacts and economic cost of transportation were considered. The overall environmental impact of county model is the lowest. Town model delivers the lowest economic cost in three models. Waste sorting was considered in scenario analysis via LCA and LCC. Abstract: The dispersed sources and inconvenient transportation of rural domestic waste (RDW) lead to difficult centralized treatment. Gasification is suitable for decentralized waste treatment, which can effectively avoid RDW long-distance transportation and reduce dioxin emissions compared with small-scale incineration. Hence, economically-affordable and environmentally-friendly RDW treatment models with different gasification scales are required, and village, town and county models were compared via life cycle assessment (LCA) and life cycle cost (LCC) methods in this study. Furthermore, scenario analysis investigated waste sorting based on two food waste (FW) treatment technologies, different FW separate collection efficiency, and electricity recovery to explore the environmental and economic improvement potentials of three models. LCA results show that electricity consumption and direct emissions are significant contributors to environmental impacts, and the county model outperforms village and town models. Moreover, transportation accounts for 6% of the overall environmental impact in the county model. Scenario analysis reveals that waste sorting and electricity recovery can reduce the overall environmental impact by 29% to 146% for three models. LCC results demonstrate that the town model delivers the lowest economic cost, while the village model is the highest. In scenario analysis, resource utilization of FW and electricity recovery of other waste exhibit promising economic benefits. The findings provide comprehensive references for sustainable RDW treatment.